2019
DOI: 10.1590/1678-4162-9797
|View full text |Cite
|
Sign up to set email alerts
|

Imunodetecção de Toxoplasma gondii em tecido placentário de cabras naturalmente infectadas

Abstract: RESUMO A imuno-histoquímica (IHQ) é considerada uma ferramenta rápida e precisa para a identificação de protozoários, como Toxoplasma gondii, em tecidos fetais e placentários. Neste estudo foi avaliada a imunodetecção de Toxoplasma gondii em tecido placentário de cabras naturalmente infectadas. Foram coletadas e analisadas 80 amostras de placentas de cabras procedentes de único rebanho com sorologia positiva para T. gondii na técnica de ELISA. Na histopatologia, 27/80 amostras apresentaram lesões sugestivas de… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 24 publications
0
3
0
Order By: Relevance
“…In the state of Paraná, Brazil, in a study on 179 goats, among which 33 had had abortions, 137 (76.53%) were serologically positive and 11 (33%) of the 33 goats with symptoms were positive in PCR (Ferreira Neto et al 2018). Mesquita et al (2019) reported on an outbreak that occurred in Alagoas in 80 animals, in which, among 27 placenta samples analyzed, 23 (85.2%) were positive in immunohistochemical tests.…”
Section: )mentioning
confidence: 99%
See 1 more Smart Citation
“…In the state of Paraná, Brazil, in a study on 179 goats, among which 33 had had abortions, 137 (76.53%) were serologically positive and 11 (33%) of the 33 goats with symptoms were positive in PCR (Ferreira Neto et al 2018). Mesquita et al (2019) reported on an outbreak that occurred in Alagoas in 80 animals, in which, among 27 placenta samples analyzed, 23 (85.2%) were positive in immunohistochemical tests.…”
Section: )mentioning
confidence: 99%
“…In Brazil, it is likely that many cases of toxoplasmosis in goats go unreported (and thus that the number of cases is underreported), due to the scarcity of studies aimed at diagnosing the causes of abortion and the absence of a standard for analyses on placental and fetal tissues (Mesquita et al 2019). Some authors have even emphasized that outbreaks may be really scarce, as shown in the literature (Moeller 2001).…”
Section: )mentioning
confidence: 99%
“…In spite of the evolution during the last decade, sheep and goat rearing is still negatively influenced by factors including inappropriate health management. Several infectious diseases are still highly prevalent in sheep and goats, especially in the Brazilian Northeast (MESQUITA et al, 2019;RÊGO et al, 2016). Toxoplasmosis is among the main diseases that cause miscarriage in sheep and goats.…”
Section: Introductionmentioning
confidence: 99%